Induction of Gamma-Glutamyltransferase Activity and Consequent Pro-oxidant Reactions in Human Macrophages Exposed to Crocidolite Asbestos. (6th August 2019) - Corti, Alessandro; Bonetti, Justine; Dominici, Silvia; Piaggi, Simona; Fierabracci, Vanna; Foddis, Rudy; Pompella, Alfonso
Abstract: Asbestos is the main causative agent of malignant pleural mesothelioma. The variety known as crocidolite (blue asbestos) owns the highest pathogenic potential, due to the dimensions of its fibers as well as to its content of iron. The latter can in fact react with macrophage-derived hydrogen peroxide in the so called Fenton reaction, giving rise to highly reactive and mutagenic hydroxyl radical. On the other hand, hydroxyl radical can as well originate after thiol-dependent reduction of iron, a process capable of starting its redox cycling. Previous studies showed that glutathione (GSH) is one such thiol, and that cellular gamma-glutamyltransferase (GGT) can efficiently potentiate GSH-dependent iron redox cycling and consequent oxidative stress. As GGT is expressed in macrophages and is released upon their activation, the present study was aimed at verifying the hypothesis that GSH/GGT-dependent redox reactions may participate in the oxidative stress following the activation of macrophages induced by crocidolite asbestos. Experiments in acellular systems confirmed that GGT-mediated metabolism of GSH can potentiate crocidolite-dependent production of superoxide anion, through the production of highly reactive dipeptide thiol cysteinyl-glycine. Cultured THP-1 macrophagic cells, as well as isolated monocytes obtained from healthy donors and differentiated to macrophages in vitro, were investigated as to their expression of GGT and the effects of exposure to crocidolite. The results show that crocidolite asbestos at subtoxic concentrations (50–250 ng/1000 cells) can upregulate GGT expression, which raises the possibility that macrophage-initiated, GSH/GGT-dependent pro-oxidant reactions may participate in the pathogenesis of tissue damage and inflammation consequent to crocidolite intoxication.